Impact of cochlear implant component upgrades on auditory performance: a longitudinal study - Salgueiro, Andressa da Costa (2025)
Introduction: Cochlear implantation is a well-established treatment for individuals with severe-to-profound sensorineural hearing loss. The device consists of an internal component and an external sound processor. However, uncertainties remain regarding auditory outcomes following internal and/or external device replacements. Objective: This study aimed to evaluate performance after cochlear implant internal and/or external component upgrades in a Brazilian public tertiary center. Methods: A longitudinal observational study was conducted in a national referral hospital for hearing health. Free-field audiometry and voice detection threshold were assessed. Speech perception was evaluated using closed-set and open-set tests. Subjective satisfaction was measured using the Net Promoter Score, the Hearing Implant Sound Quality Index, and the Children with Cochlear Implants: Parents Perspective questionnaire. Results: A total of 176 cochlear reimplantation procedures and 282 external sound processor upgrades were analyzed. Longitudinal analysis showed significant improvements in auditory thresholds and voice detection in several groups. Most participants demonstrated either stability or improvement in speech perception. High satisfaction levels were reported regarding current sound processor use, speech-in-noise perception, music enjoyment, and post-reimplantation outcomes. Caregivers of young children also reported positive impacts on quality of life. Conclusion: Both cochlear reimplantation and external processor updates were associated with measurable improvements in auditory performance and user satisfaction. These findings support the systematic renewal of cochlear implant technologies in public health programs to optimize long-term outcomes.